Taking stock of Niger’s existing regional and global trade agreements - Traoré, Fousseini (Wageningen Academic Publishers, 2018)
This chapter examines the global and regional trade agreements signed by Niger, their implementation status, and the main obstacles to their full implementation. For the agreements that involved strong commitments by Niger, the results are mixed in terms of implementation. For tariff related measures, Niger has implemented all its commitments with the exception of the recent violations of its WTO bound tariffs following the introduction of the ECOWAS Common External Tariff (CET). As for non-tariff commitments, Niger has made considerable progress although there is room for improvement. It has put in place most of the institutions needed to implement the agreements and adapted its legislation accordingly, in particular to comply with the Sanitary and Phytosanitary Measures, the Technical Barriers to Trade Agreement and the sub-regional regulations under both ECOWAS and WAEMU. The creation of the National Standardisation Council (CNN) as well as the National Board for Ensuring Conformity with Standards (AVCN) are in pursuit of this objective. With regard to custom valuation, with a few exceptions, the country applies the transaction value principle, in accordance with the WTO custom valuation agreement, and WAEMU and ECOWAS regulations. The main challenges for customs are related to the new Trade Facilitation Agreement (TFA) adopted at the Bali Conference in 2013. The private sector needs support in building capacities to comply with international norms and standards. Also supply-side constraints (poor road and transport infrastructure, ineffective telecommunication services) should be addressed so that the country can take advantage of the liberalisation process.